(untitled) (Biological Sciences - PJSIR, 2001)
The viscosity and electrical conductance of some Nigerian traditional soaps and their separate mixtures with sodium chloride and calcium chloride have been examined. The activation energies of viscous flow and of electrical conductance were evaluated from viscous and conductance data respectively. Results on viscous flow suggest structural similarities between the soaps examined. The halides used enhanced the electrical conductance ofthe soaps in solution and hence the halides can be used to dope the conducting ability of the soaps. The soap solution thus doped could be used industrially as electrolyte, an economic use to which the soaps has not been put hitherto,